Measurement of glass transition in native wheat flour by dynamic mechanical thermal analysis (DMTA) - Pereira, Pedro M. (2011)
This work describes a method to study glass transition on native starch powders, based on dynamical mechanical thermal analysis using compression tests, and was applied to wheat flour (13.5% water content). This method will allow the determination of Tg in native (unprocessed) starchy materials, with minimal disturbance of the natural structures. The influence of the test conditions (heating rate, frequency and strain) on the glass transition measurements was determined using factorial designs. The values of Tg determined as the maxima of the energy dissipation (peaks in E ) of native flour and of freezedried pre-gelatinized flour were not statistically different (around 64 C). The heating rate did not affect the measurements in the range tested (0.25 to 1 C min 1). An interactive effect of the strain amplitude and the frequency was detected. The significance of this interaction can be caused by differences in mechanical energy dissipation, which would indicate that not only temperature but also the total energy input may affect this transition. Slight effects of phase separation between gluten and starch were found on native flour.